Penelitian Praktis Model Blanded Learning Berbasis SPOC pada Matematika Tingkat Lanjut - Wang, Fang; Du, Wen (Edumatica : Jurnal Pendidikan Matematika, 2024)
Based on the current situation of advanced mathematics curriculum teaching, this study first constructs a blended learning model for advanced mathematics based on SPOC through literature research from three aspects: curriculum design, teaching implementation, and learning evaluation. And designs a specific blended teaching case combined with the "definite integral concept". Then, we conducted a purposeful sampling in a public school called Qinghai Normal University and selected 82 students from two first-year classes majoring in biotechnology as the research objects, and carried out an 18-week empirical study with experimental control. Finally, the final grades and teaching evaluation questionnaires of students in advanced mathematics were collected for data processing and analysis. The research results showed that students in the SPOC blended learning class had better math scores than those in the traditional teaching class, and blended learning could narrow the gap in students' math proficiency. At the same time, the questionnaire survey found that students believe that blended learning in advanced mathematics courses has abundant resources, frequent interaction and communication, and can improve learning efficiency. However, traditional advanced mathematics learning puts a lot of pressure, and they are busy taking notes in the classroom and cannot respond to the teacher's questions in time.